2017
DOI: 10.1021/acs.jafc.7b03762
|View full text |Cite
|
Sign up to set email alerts
|

Saffron against Components of Metabolic Syndrome: Current Status and Prospective

Abstract: Saffron, the dried stigmas of Crocus sativus L., is mainly used as a food coloring and flavoring agent. This agricultural product is used in traditional medicine for the treatment of several diseases including asthma, liver disease, menstruation disorders, and, of special interest in this review, metabolic syndrome. Saffron and its active components including crocin, crocetin, and safranal are potential therapeutic candidates for attenuating MetS complications including hypertension, hyperglycemia, obesity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…Finally, the present results clearly indicate that crocin exhibited preventive activities against both MetS as well as the resultant osteoporosis. This is consistent with previous reports highlighting crocin's activities against MetS (Javandoost et al, ; Kermani et al, ; Shafiee et al, ). Thus, the primary preventive activity of crocin can be considered as a complementary element in the observed antiosteoporotic activities.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Finally, the present results clearly indicate that crocin exhibited preventive activities against both MetS as well as the resultant osteoporosis. This is consistent with previous reports highlighting crocin's activities against MetS (Javandoost et al, ; Kermani et al, ; Shafiee et al, ). Thus, the primary preventive activity of crocin can be considered as a complementary element in the observed antiosteoporotic activities.…”
Section: Resultssupporting
confidence: 94%
“…Thus, it is noteworthy to report that crocin protected against all pathological changes in the MetS‐related parameters. This is consistent with previous reports emphasizing the ability of crocin contained in saffron to protect against different MetS components (Shafiee et al, ).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Saffron decreases systolic blood pressure and mean arterial pressure (Ghaffari & Roshanravan, 2018) through it vaso-modulating effects and anti-inflammatory effects. It also exerts its therapeutic effects via its lipid-lowering effects (Shafiee et al, 2017). Other mechanisms of action include regulating the expression of growth factors such as adiponectin, tumor necrosis factor-α, and leptin in adipose tissue or fat mass (Ghaffari & Roshanravan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews evaluating the effects of saffron have reported evidence to support the beneficial effects for weight, HDL, and LDL (Bukhari et al, 2018;Ghaffari & Roshanravan, 2018;Rahaiee, Moini, Hashemi, & Shojaosadati, 2015;Shafiee et al, 2017). However, most of the evidence from these reports are from animal studies and do not provide evidence of causal effects.…”
Section: Discussionmentioning
confidence: 99%